The Safety and Efficacy of KAI‐1678— An Inhibitor of Epsilon Protein Kinase C (εPKC)—Versus Lidocaine and Placebo for the Treatment of Postherpetic Neuralgia: A Crossover Study Design. Issue 4 (25th February 2013) - Cousins, Michael J.; Pickthorn, Karen; Huang, Saling; Critchley, Linda; Bell, Gregory
Abstract Objective. Postherpetic neuralgia (PHN) occurs in approximately 10–20% of patients with herpes zoster, and the risk increases with age. In this clinical trial, we evaluated the analgesic properties of KAI‐1678—an inhibitor of epsilon protein kinase C—in the treatment of neuropathic pain in patients with PHN. Design. The study was a three‐treatment period, double‐blind, randomized, placebo and active comparator crossover trial evaluating subcutaneous infusions of KAI‐1678 (25 mg), placebo, and lidocaine hydrochloride (700 mg; active comparator). Patients. A total of 17 men and 6 women (N = 23) were enrolled after fulfilling diagnosis of PHN with pain persisting for ≥3 months after a segmental herpes zoster eruption. Patients had to have a mean average pain score of ≥4 points on an 11‐point numerical rating scale (NRS; ranging from 0 to 10) based on at least three daily entries prior to participation in the subsequent treatment period. Results. Overall, administration of KAI‐1678 was generally safe and well tolerated. However, compared with placebo, KAI‐1678 did not improve clinical pain scores as recorded using the NRS (0–10). In contrast, subcutaneous infusions of lidocaine were associated with a significant reduction in pain intensity at the end of the infusion. Conclusions. We conclude that KAI‐1678 is not efficacious as an acute analgesic for chronic neuropathic pain because of PHN. However, for the first time, the results demonstrate that subcutaneous infusions of lidocaine are effective in treating neuropathic pain. The results of lidocaine treatment also indicate that the crossover study design was adequate to detect a clinically meaningful response in this analgesia study.